Effectiveness of the Strengthening Families Programme in the UK at preventing substance misuse in 10–14 year-olds: a pragmatic randomised controlled trial. Issue 2 (21st February 2022) - Segrott, Jeremy; Gillespie, David; Lau, Mandy; Holliday, Jo; Murphy, Simon; Foxcroft, David; Hood, Kerenza; Scourfield, Jonathan; Phillips, Ceri; Roberts, Zoe; Rothwell, Heather; Hurlow, Claire; et al.
Abstract : Objectives: The Strengthening Families Programme 10–14 (SFP10-14) is a USA-developed universal group-based intervention aiming to prevent substance misuse by strengthening protective factors within the family. This study evaluated a proportionate universal implementation of the adapted UK version (SFP10-14UK) which brought together families identified as likely/not likely to experience/present challenges within a group setting. Design: Pragmatic cluster-randomised controlled effectiveness trial, with families as the unit of randomisation and embedded process and economic evaluations. Setting: The study took place in seven counties of Wales, UK. Participants: 715 families (919 parents/carers, 931 young people) were randomised. Interventions: Families randomised to the intervention arm received the SFP10-14 comprising seven weekly sessions. Families in intervention and control arms received existing services as normal. Outcome measures: Primary outcomes were the number of occasions young people reported drinking alcohol in the last 30 days; and drunkenness during the same period, dichotomised as 'never' and '1–2 times or more'. Secondary outcomes examined alcohol/tobacco/substance behaviours including: cannabis use; weekly smoking (validated by salivary cotinine measures); age of alcohol initiation; frequency of drinking >5 drinks in a row; frequency of different types of alcoholic drinks; alcohol-related problems. Retention: primary analysis included 746 young people (80.1%) (alcohol consumption) and 732 young people (78.6%) (drunkenness). Results: There was no evidence of statistically significant between-group differences 2 years after randomisation for primary outcomes (young people's alcohol consumption in the last 30 days adjusted OR=1.11, 95% CI 0.72 to 1.71, p=0.646; drunkenness in the last 30 days adjusted OR=1.46, 95% CI 0.83 to 2.55, p=0.185). There were no statistically significant between-group differences for other substance use outcomes, or those relating to well-being/stress, and emotional/behavioural problems. Conclusions: Previous evidence of effectiveness was not replicated. Findings highlight the importance of evaluating interventions when they are adapted for new settings. Trial registration number: ISRCTN63550893 .Cite Now